Troop movement and food habits of white-faced monkeys in a tropical-dry forest - Moscow, Daniel; Vaughan, Cristopher (Revista de Biología Tropical, 1987)
Home-range, movement and activity patterns and diet of a group of 16 white-faced monkeys (Cebus capucinus) were studied in a Costa Rican tropical dry forest at the end of the dry season (March and April) of 1982. The troop used an area of .67 km2 and moved an average of 4.5 km ± 0.6 daily. Three basic daily activities were identified: resting, moving and feeding. Resting was greatest between 1000-1500 hours. Movement, which was strongly correlated with feeding, occurred most between 0500-0900 hrs and 1300-1800 hrs. The primates were omnivores, feeding on parts of 27 species of plants, four species of insects and an Anolis lizard.